INBOUND AND OUTBOUND TRAFFIC CONTROLLING OF MULTI-HOMED AUTONOMOUS SYSTEM - Pramartha, Cokorda Rai Adi (Jurnal Ilmu Komputer; Vol 4 No 1: April 2011, 2011)
A multi-homed Autonomous System (AS) usually has two or more BGP border routers connected to the other AS. This border router is the gateway for the AS to connect with other AS. Having more than one gateway is an obstacle for the multi-homed AS when setting their outbound and inbound traffic. The research and observation have been at a multi-homed AS indicating that the BGP Routing Protocol can overcome these obstacles. Multi-homed AS can use the prepend method and set the local_preference attribute to control outbound and inbound traffic.
Keywords: -